Hygrothermal behavior of a massive wall with interior insulation during wetting. (July 2015) - Guizzardi, M.; Derome, D.; Vonbank, R.; Carmeliet, J.
Abstract: To improve the energy efficiency of historical buildings, the introduction of an interior insulation is often the only possible solution in order to preserve their valuable external facades. However, this intervention changes the wall hygrothermal conditions and can negatively affect its hygrothermal performance. Furthermore, interior insulation is often difficult to apply due to practical problems of irregularities in geometry and heterogeneity of materials. A newly developed high insulating render is used as interior insulation on a masonry test wall and is exposed to controlled but severe wetting conditions, while the hygrothermal parameters in its different components have been recorded. In addition to provide a well-documented dataset for model validation, this investigation highlights the hygrothermal behavior of a masonry wall internally insulated with a new developed highly insulating render. The experimental work described in the present paper is designed in order to record data to be used for the validation of a numerical model for the parametric study of the hygrothermal behavior of internally insulated masonry walls. Highlights: Hygrothermal behavior of an internally insulated masonry wall. Moisture content, relative humidity and temperature changes. Effects of retrofit interventions of historical buildings.